Chemical composition and bioreactivity of PM2.5 during 2013 haze events in China. (February 2016) - Ho, Kin-Fai; Ho, Steven Sai Hang; Huang, Ru-Jin; Chuang, Hsiao-Chi; Cao, Jun-Ji; Han, Yongming; Lui, Ka-Hei; Ning, Zhi; Chuang, Kai-Jen; Cheng, Tsun-Jen; Lee, Shun-Cheng; Hu, Di; et al.
Abstract: Chemical composition and bioreactivity of PM2.5 samples collected from Beijing (BJ), Xi'an (XA), Xiamen (XM) and Hong Kong (HK) in China during haze events were characterized. PM2.5 mass concentrations in BJ, XA, XM and HK in the episodes were found to be 258 ± 100 μg m −3, 233 ± 52 μg m −3, 46 ± 9 μg m −3 and 48 ± 13 μg m −3, respectively. Significant increase of sulfate, nitrate and ammonium concentrations in northern cities were observed. High contributions of biomass burning emissions to organic carbon (OC) in northern cities were estimated in this study implying frequent biomass burning during the haze periods. The urea concentrations in PM2.5 were 1855 ± 755 ng m −3 (BJ), 1124 ± 243 ng m −3 (XA), 543 ± 104 ng m −3 (XM) and 363 ± 61 ng m −3 (HK) suggesting higher or close to upper limits compared to other regions in the world. Dose-dependent alterations in oxidative potential, IL-6, IFN-γ and TNF-α levels were also investigated. The oxidative potential levels are BJ > XM > XA > HK, whereas levels of IL-6, IFN-γ and TNF-α were BJ > XA > XM > HK. The sulfate, nitrate, ammonium, OC, urea and levoglucosan are associated with oxidative-inflammatory responses. These experimental results are crucial for the policymakers to implement cost-effective abatement strategies for improving air quality. Highlights: Significant increases of sulfate, nitrate and ammonium were observed during episodes. High contributions of biomass burning emissions to organic carbon (OC) were estimated in this study. BJ PM2.5 samples has the highest bioreactivity although PM2.5 levels are not the highest. The OC, urea and levoglucosan are associated with oxidative-inflammatory responses.